Truthful revelation mechanisms for simultaneous common agency games - Alessandro Pavan; Giacomo Calzolari (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2008)
This paper considers games in which multiple principals contract simultaneously with the same agent. We introduce a new class of revelation mechanisms that, although it does not always permit a complete equilibrium characterization, it facilitates the characterization of the equilibrium outcomes that are typically of interest in applications (those sustained by pure-strategy pro.les in which the agent.s behavior in each relationship is Markov, i.e., it depends only on payoþ-relevant information such as the agent.s type and the decisions he is inducing with the other principals). We then illustrate how these mechanisms can be put to work in environments such as menu auctions, competition in nonlinear tariþs, and moral hazard settings. Lastly, we show how one can enrich the revelation mechanisms, albeit at a cost of an increase in complexity, to characterize also equilibrium outcomes sustained by non-Markov strategies and/or mixed-strategy profiles.
Keywords: D89; C72; 330; Mechanism design; contracts; revelation principle; menus; endogenous payoff-relevant information.